Electronic structure and magnetism on FeSiAl alloy: A DFT study - Cardoso Schwindt, Virginia Araceli (2015)
Density functional theory (DFT) calculation has been performed to study the electronic structure and chemical bonding in FeSiAl alloy. These calculations are useful to understand the magnetic properties of this alloy. Our results show that the mean magnetic moment of Fe atoms decreases due to the crystal structure and the effect of Si and Al. Depending on the environment, the magnetic moment of one Fe site (Fe1) increases to about 14.3% while of the other site (Fe2) decreases to about 25.9% (compared with pure bcc Fe). All metal?metal overlap interactions are bonding and slightly weaker than those found in the bcc Fe structure. The electronic structure (DOS) shows an important hybridization among Fe, Si and Al atoms, thus making asymmetric the PDOS with a very slight polarization of Al and Si atoms. Our study explains the importance of crystal structure in determining the magnetic properties of the alloys. FeSiAl is a good candidate for electromagnetic interference shielding combining low price and good mechanical and magnetic properties.